Long-Term Experiences of Basic Education in Laboratory Animal Science - Valeria Küller; Johannes Schenkel (Animals)
Adequate education in laboratory animal science and subsequently the attendance of relevant courses are mandatory prerequisites for animal experimentation. The course content for different stakeholders is stipulated by European and national regulations. If all of this content is covered, accreditation by competent bodies is possible and recommended. Here, we present our experiences with an EU-Function A/C/D accredited course (practical training with mice and rats) and an introductory seminar for undergraduate students, which have been running for more than ten years. All courses were organized in-house and were very relevant to the students and their needs but were also very labor intensive. The courses were systematically (and retrospectively) evaluated, showing a high degree of satisfaction and a great acquisition of knowledge, and the organizer was able to re-adjust the courses as needed over the years. Tests demonstrated the students’ progress and highlighted some parts of the lessons that were difficult to convey, such as those on legal regulations, housing and feeding, transport, GM animals, breeding, and the classification of severity. Dummies were proven to be very helpful at the beginning of the training but could not fully replace training with live animals. On-site lectures were favored over online sources, which were needed due to the pandemic. High standards in education are mandatory, and the accreditation process allows for the transferal of certificates to other institutions.